Deliberate self-harm in adolescents: comparison between those who receive help following self-harm and those who do not. - Ystgaard, M; Arensman, E; Hawton, K; Madge, N; van Heeringen, K; Hewitt, A; de Wilde, E; De Leo, D; Fekete, S (2009)
This international comparative study addresses differences between adolescents who engage in deliberate self-harm (DSH) and who receive help following the DSH episode versus those who do not. A standardised self-report questionnaire was completed by pupils aged 14-17 in Australia, Belgium, England, Hungary, Ireland, The Netherlands, and Norway (n=30,532). An act of DSH in the year prior to the study was reported by 1660 participants. Nearly half (48.4%) had not received any help following DSH, 32.8% had received help from their social network only and 18.8% from health services. Except for Hungary, cross-national comparisons revealed remarkably similar findings. Adolescents who had been in contact with health services following DSH reported more often a wish to die, lethal methods, alcohol/drug problems and DSH in the family compared to those who had not. However, those who received no help or help from their social network only were also heavily burdened.